El aceite bético durante el Bajo Imperio - Remesal Rodríguez, José (Antigüedad y Cristianismo, 1991)
The author defende the hypothesis of the survival of the production and esportation of the oil produced in the Baetica in the Late Empire (the third, fourth and fifth centuries) in the light of the arqueological sources. (Dressel amphores 23 found in Ostia, Ampurias, El Tejarillo, the church of St. Gereon in Köln, the circus of Magencius in Rome and in Tarragona). The entire subject is related to the political and economical evolution during the period between Septimius Severus and Docletianus, and especially to the organic segmentation with the resulting creation of a system of inter provincial relations during the Diocletian eppoch, which introduces changes in the oil market in the Baetica.